The Impact of Organizational Climate of College and Hospital Libraries of Medical Sciences Universities on Librarians\' Job Burnout - Fatemeh Sadat Zaribaf; Fatemeh Sheikhshoaei; Seyed Javad Ghazimirsaid Ghazimirsaeed (Tehran University of Medical Sciences, 2019)
Background and Aim: Considering the effect of organizational climate on work motivation, not using the librarians who have a satisfactory feeling about their job can cause irreversible damages to the library. Therefore, the aim of this study is to determine the effect of organizational climate of college and hospital libraries on the burnout of librarians working there. Materials and Methods: This is an applied research and a descriptive-analytical survey. One hundred seventy-seven librarians from faculties and hospital libraries affiliated to Tehran, Iran and Shahid Beheshti Universities of Medical Sciences were surveyed by census method in 2019. Data collection instruments were Halpin and Croftchr('39')s organizational climate and Maslach and Jackson job burnout questionnaires. The validity was confirmed by 3 experts and the reliability by Cronbachchr('39')s alpha coefficient. For data analysis, SPSS software, and descriptive and analytical statistics were used. Results: The findings showed that the mean of organizational climate was at a desirable level (3.4)  and the average of job burnout was 1.7; therefore, the job burnout status of librarians is desirable because it is a negative variable. Also, the components of organizational climate predict 41% of job burnout variable. Among demographic characteristics, job burnout variable varies only in terms of field of study, and organizational climate only in terms of the type of library. Conclusion: In general, the organizational climate status and job burnout status of the studied libraries are desirable; also, organizational climate components affect job burnout.